Implementasi Kebijakan Pinjaman Daerah Di Kabupaten Buton Selatan - abidin, zainul (Inovasi, 2025)
This study aims to describe the substance and implementation of the regional loan policy in South Buton Regency. Data were collected through interviews, observations and document review. Data were analyzed interactively starting from data collection, classification, reduction to conclusion drawing. The results showed that the Regional Loan Policy of South Buton Regency had a clear policy substance. The policy objective is to develop port and health infrastructure to improve public services in the field of sea transportation and improve health services which are also expected to increase the achievement of local revenue in the future. The main policy implementers are the Department of Transportation and the South Buton District Hospital.  The stages or process of the South Buton Regency Regional Loan are carried out based on clear processes and stages starting from the district government level, the Southeast Sulawesi provincial government, to the central government through the Ministry of Home Affairs and the Ministry of Finance of the Republic of Indonesia. In its implementation, there are still some findings of weaknesses in both administration and physical work in the application of the principle of obeying the rules and regulations, the principle of accountability and the principle of prudence. This is indicated by the many addendums to the budget ceiling due to planning errors and also the many findings of the Supreme Audit Agency on financial reports related to activities sourced from regional loan budgets. There were also cases of loan principal defaults due to a shift in budget allocation from the original allocation of loan principal repayment funds to activities that became the aspirations of the regional head. The performance indicators of the regional loan policy are problematic in the three aspects assessed, namely the deadline, the physical output of work and non-physical in this case including the activity implementation report. The causes are first, planning errors in the early stages at the Transportation Agency. Keywords:  implementation, policy, regional loan